2 + 2 = Streptococcus - Nibungco, Gabriel Francisco (Ars Medica, 2025)
Medical knowledge is a lens through which one can encounter the world, but the world, especially our own deeply personal memories, beliefs, and commitments, also has much to say about how we encounter, and practice medicine. This essay is a reflection on the subjective and the objective and how intimately related they are in the practice of healthcare.